Brand Equity and Stock Performance in Indonesia During the Stock Market Crash Period in 2020 - Suryadinata, Andre; Kim, Sung Suk (Universitas Pelita Harapan, 2023)
We study the relationship between brand equity and stock return in the Indonesian market during the market crash period (March 5th–March 24th, 2020). Using the brand valuation published in “Top 100 Most Valuable Brands” in Indonesia 2020 by Brand Finance, we find that during the crash period, stocks with high brand equity have significantly negative returns with significantly higher systematic risk. We continue further by also analyzing the non-crash period in 2020. We find that in 2020 as a whole, stocks with high brand equity will provide significantly higher returns while at the same time having significantly higher systematic risk compared to other stocks with lower brand equity.